2019
DOI: 10.1002/asia.201901086
|View full text |Cite
|
Sign up to set email alerts
|

A Strongly Fluorescent Molecular Material Responsive to Physical/Chemical Stimuli and their Coupled Impact

Abstract: Molecular materials with weak but extended and pliable supramolecular interactions are versatile candidates for eliciting stimuli-sensitive optical responses. An ovel diaminodicyanoquinodimethane (DADQ) molecule,7 ,7-bis(2-(2pyridyl)ethylamino)-8,8-dicyanoquinodimethane (BPEDQ), has been synthesized and structurally characterized; it exhibits enhanced fluorescencee mission in the aggregated and solid states,c haracteristico fD ADQs.T he pyridine moieties in the molecule, in addition to the amino and cyano grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…[3] To achieve efficient emission in the solid state, a few strategies have been adopted that includes introducing sterically bulky or dentric substituents on the planar π-conjugated systems, [4] tuning the charge transfer properties of donor-acceptor systems [5,23,24] and introducing AIE (aggregation-induced emission) active molecules on wellknown ACQ (aggregation-caused quenching) chromophores. [3][4][5][6][7][8][9][10] Further, various kinds of intermolecular interactions like NÀ H-π, π-π, halogen bonding and hydrogen bonding are known to elicit strong emission in specific fluorophores. [6] Few classes of molecules like tetraphenylethylene, [3,7] tetraarylaminoborane, [8] hexaphenylsilole [3,9] and diaminodicyanoquinodimethane [10] derivatives showed efficient blue emission in the solid state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] To achieve efficient emission in the solid state, a few strategies have been adopted that includes introducing sterically bulky or dentric substituents on the planar π-conjugated systems, [4] tuning the charge transfer properties of donor-acceptor systems [5,23,24] and introducing AIE (aggregation-induced emission) active molecules on wellknown ACQ (aggregation-caused quenching) chromophores. [3][4][5][6][7][8][9][10] Further, various kinds of intermolecular interactions like NÀ H-π, π-π, halogen bonding and hydrogen bonding are known to elicit strong emission in specific fluorophores. [6] Few classes of molecules like tetraphenylethylene, [3,7] tetraarylaminoborane, [8] hexaphenylsilole [3,9] and diaminodicyanoquinodimethane [10] derivatives showed efficient blue emission in the solid state.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] Further, various kinds of intermolecular interactions like NÀ H-π, π-π, halogen bonding and hydrogen bonding are known to elicit strong emission in specific fluorophores. [6] Few classes of molecules like tetraphenylethylene, [3,7] tetraarylaminoborane, [8] hexaphenylsilole [3,9] and diaminodicyanoquinodimethane [10] derivatives showed efficient blue emission in the solid state. In recent times, phosphorescent materials have received considerable attention due to their potential applications in displays, solid state lighting, optical storage and sensors.…”
Section: Introductionmentioning
confidence: 99%
“…This results in divergent applications such as organic semiconductors, 4 molecular hopper crystals, 5 non-linear optical [6][7] and mechanochromic materials. 8 Di-substituted TCNQ derivatives [9][10][11] usually display enhanced fluorescence in their solids;…”
Section: Introductionmentioning
confidence: 99%
“…[13] Size dependent optical and morphological studies revealed interesting results from simple aromatic amine substituted TCNQ's. [14][15][16] Recently, aromatic (benzene) amine moieties as substituents on TCNQ resulting in cyclized structures at δ + carbon has evolved in high fluorescent diaminodicyanoquinones, with 90 % quantum yields. [17] High aspect ratio nanowires of Ag/AgTCNQ synthesized on silver fabric for the first time have shown antimicrobial property.…”
Section: Introductionmentioning
confidence: 99%
“…Mostly, TCNQ derivatives have shown enhanced emission in solid/aggregated/thin film state rather than their solutions, probably due to the strong zwitterion and push‐pull nature, [12–13] supramolecular assembly, [10–13] restricted intra molecular rotations [12] and non‐radiative geometrical relaxations in excited states [13] . Size dependent optical and morphological studies revealed interesting results from simple aromatic amine substituted TCNQ's [14–16] . Recently, aromatic (benzene) amine moieties as substituents on TCNQ resulting in cyclized structures at δ + carbon has evolved in high fluorescent diaminodicyanoquinones, with 90 % quantum yields [17] …”
Section: Introductionmentioning
confidence: 99%